A DATA-DRIVEN ANALYSIS OF THE IMPACT OF THE DIGITAL RENMINBI ON MULTILATERAL CURRENCY SWAP AGREEMENTS WITH COUNTRIES IN THE ISLAMIC WORLD - Yu, Shanxuan (UIN Raden Mas Said Surakarta, 2023)
China was once among the world's poorest countries, but during the past forty years, it has turned into an economic powerhouse. Bilateral exchange lines are one of PBC's patented methods of promoting RMB internationalization. Swap lines were initially created to assist with RMB settlement in international trade due to the limited RMB liquidity overseas. Prior to eventually expanding to other rising economies, the first geographic reach concentrated on Asian neighbors. Swap lines can boost a loan's usage and reduce the apparent risk distribution of a loan in a rising currency. Swap lines have an impact that extends beyond their core usage in order to create a larger safety net. The PBC has established bilateral swap lines in addition to offshore clearing institutions in 25 markets to facilitate RMB payments. The e-CNY was created by the PBC for four main reasons. The general public's accessibility to digital money is the initial objective of the e-CNY. Additionally, it aspires to promote efficient, secure, and equitable retail payment systems. Third, the e-CNY will improve the efficiency of international payments. The fourth is that financial inclusion should be benefited. The empirical analysis underlined the crucial hopes that the e-CNY may promote bilateral currency exchanges between Islamic nations and China and may serve as a big economic boost for those nations.